PENINGKATAN KETERAMPILAN BERBICARA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE THINK PAIR SHARE DI KELAS V SD NEGERI 13 KOTO BARU KECAMATAN KUBUNG KABUPATEN SOLOK - Reni Guswita; Subhanadri Subhanadri (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The background of this research is the low speaking skills of the fifth grade students of SD Negeri 13 Koto Baru. The purpose of this study is to describe the planning, implementation and improvement of speaking skills using the cooperative model think pair share in class V SD Negeri 13 Koto Baru Kecamatan Kubung Kabupaten Solok. The type of research used in this research is Classroom Action Research. The research was conducted at SD Negeri 13 Koto Baru Kecamatan Kubung Kabupaten Solok. The research was conducted in the second semester, namely May-June 2017, carried out in 2 cycles consisting of two meetings. Each cycle consists of 4 stages, namely planning, acting, observing, and reflecting. The subjects of this study were students of class V with a total of 12 students. The data collection tools used were observation guidelines, tests and documentation. The result of this research is that speaking skills using the cooperative model of the think pair share type have increased, especially in using the right choice of words, pronunciation, intonation, stress, and expression. In the first cycle of meeting I, the students' speaking skills were 60.7%, increasing in the first cycle of the second meeting to 67% with a completeness level of 41.7%. Likewise in the second cycle of meeting I students' speaking skills increased to 72.3% and meeting II became 80.1% with a completeness level of 83.3%. It is suggested that teachers should be able to apply learning speaking skills using the Think Pair Share type cooperative model.